Mine Planning and Equipment Selection 2014
DOI: 10.1007/978-3-319-02678-7_61
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Spontaneous Combustion of Coal in Underground Coal Mining

Abstract: Abstract. The risk of spontaneous combustion of coal is highly serious especially for underground coal mines. Coals react with oxygen immediately after producing in coal mines and they are subject to spontaneous combustion. This reaction is an exothermic reaction and coals give heat to the surrounding air. If the heat is not removed from the surrounding air, spontaneous combustion occurs and then flaming fire starts. In addition, in underground coal mine besides exothermic reactions, hazardous, explosive and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The results of Graham's ratio are shown in Table 2. According to Ozdeniz et al (2014) [8] shows different ranges of combustion risk for longwall coal mine that are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of Graham's ratio are shown in Table 2. According to Ozdeniz et al (2014) [8] shows different ranges of combustion risk for longwall coal mine that are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Auto-oxidation or spontaneous combustion of coal is a serious problem that leads various safety problems in mining, long distance transportation and storage areas as well as economic losses [3] [4]. It is a self heating process that occurs when oxygen reacts with coal without influences of any external heat by which it produces various toxic gases likely CO, CO 2 , CH 4 and water vapor [5]- [8] that are harmful for any kind of coal mine and decomposition of these materials leading to the liberation of heat [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-heating in coal stockpiles usually occur in the long-term storage of thermal power stations, in open cast mines, underground old workings, highwall, waste dumps and transportation in cargo ships or trains covering long distances (Carras and Young 1994;Moghtaderi et al 2000;Zhu et al 2013). Due to the high cost of running industrial scale tests and the period required to run one experiment, limited industrial scale tests have been reported for a better understanding on the mechanism of self-heating in large-scale tests (Cliff et al 1998;Ozdeniz et al 2011Ozdeniz et al , 2014Ozdeniz and Sensogut 2006). Coal stockpiles experience low self-heating which minimizes the calorific value and the amounts of coal stocked.…”
Section: Areas Of Coal Self-heatingmentioning
confidence: 99%
“…In the case of this study excavation in the opencast areas create "breakthroughs" into the underlying mined out areas causing spontaneous combustion. Spontaneous combustion of coal pillars occur when the coal reacts with oxygen causing an exothermic reaction (Ozdeniz, Sivrikaya , & Sensogu, October 2013). …”
Section: Introductionmentioning
confidence: 99%